Community Engagement in The Telehealth Service for Aged People with Diabetes: COVID-19 response in Bangladesh - Mohammad Shamsal Islam; Bimal Chandra Das; Mohammad Musa Meah; Sanjoy Kumer Paul; Ashim Kumar Saha; Reaz Uddin Chowdhury; Mahfuz Ashraf; Salim Mahmud Chowdhury; Kazi Taznahel Sultana Ahona; Sahedul Islam Bhuiyan (ACHSM, 2021)
Purpose: The purpose of this study is to present a better understanding of the specialized telehealth service in Bangladesh from the service provider and service recipients by aged people Method: Both quantitative and qualitative methods were used to collect data from Diabetes Mellitus (DM) patients. Data were collected by online telephone interviewing with an interview schedule. A total of 100 aged people with diabetes were selected purposively for a quantitative interview and 10 In-depth Interviews (IDIs) & Key Informant Interviews (KIIs) were conducted. Result: The majority of patients aged was between 61 to 68 years with a mean age of 63.6 ± 7.01years. The difference of age of DM patients by sex was found statistically significant (x2 = 39.49, df = 31; Cramer's V = .032; P=<.003). The main source of information about digital health was: relatives (55%), neighbors (31%), television (12%), newspaper (10%), social media (9%), and healthcare providers (6%). Strong relationship was found between age of respondents and sources of information (x2= 77.08; Cramer's V= .032, df = 13; Sig; P= < .009). About 59% of DM patients were benefited from telehealth services during COVID-19, however; they encountered some difficulties like effective access to digital technology, cost, and diagnosis facilities. About 83% of respondents suggest formalizing community engagement programs to extend the digital health services during a health emergency. The common barriers to the engagement of community people in digital health care are lack of social awareness, lack of peer group support, and gender disparities. Poor counseling, language barrier, bad internet signal, and lack of family members' support were the key barriers during teleconsultation services. Conclusion: Telehealth has the potential to address critical health issues of aged people and effective community engagement may be the best option to reach older people with diabetes in Bangladesh during any health emergency.